Perbedaan Kecerdasan Emosi Komunitas Poppunk Dan Komunitas Metal (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2020)
The purpose of this study is to see significant differences in the emotional intelligence of the poppunk music community and the metal music community in Salatiga. This type of research uses a comparative causal method, which compares two groups of individuals using a cross sectional approach, the research activities carried out at one time against several groups Based on the type of ordinal data from the calculation of distributed questionnaires, and the analysis plan using statistics, this study is included in the type of quantitative research. This study chose 79 subjects which were divided into 2 groupsof the music community, 42 people inthe poppunk mucic community and 37 in the metal music community. The scale use for this study is the emotional intelligences scale compiled based on Bar-On theory, consisting of 39 items of statement taht have been tested for validity and reliability. The analysis technique in the study use the Mann Whitney Test. The result of this study indicate that no significant difference in the emotional intelligences of the communty between poppunk music and metal music community. This is indicated by the result of the mann whitney test, obtained a P-Value (Sig.2-tailed) 0,423 > greater than ? = 0,05, with thus it can be concluded that “there is no significant difference in emotional intelligence in the music poppunk community and music metal community”.